2008
DOI: 10.1108/14777280810886364
|View full text |Cite
|
Sign up to set email alerts
|

What's happening in coaching and mentoring? And what is the difference between them?

Abstract: PurposeThe purpose of this paper is to provide a summary of the latest developments in the field of corporate coaching and mentoring.Design/methodology/approachProvides a viewpoint on the coaching and mentoring field drawing on research from Europe and the US.FindingsStructured or supported coaching and mentoring within organisations is evolving rapidly and research is at last beginning to provide valuable insights into effective practices. Some strongly‐held assumptions are being challenged along the way. Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 0 publications
0
42
0
3
Order By: Relevance
“…Pero existe cierta confusión entre los términos mentoría y coaching que es necesario aclarar. Según Garvey, Stokes y Megginson (2014), estos dos conceptos muestran una relación jerárquica entre una persona con más experiencia o conocimiento y otra con menos competencia o experiencia; para otros autores, como Clutterbuck (2008), sin embargo, cada vez es más claro que coaching y mentoría deben ser defi nidos de manera diferente, relacionando el primero con el rendimiento en algún aspecto del trabajo o de la vida, y asociando al segundo más con el desarrollo integral y la promoción profesional. Ahondando más en esta distinción, Luecke (2004, p. 78) se decanta por una diferenciación respecto a su ámbito de aplicación.…”
Section: El Concepto De Mentoría Y Su Adecuación Al áMbito De La Formunclassified
“…Pero existe cierta confusión entre los términos mentoría y coaching que es necesario aclarar. Según Garvey, Stokes y Megginson (2014), estos dos conceptos muestran una relación jerárquica entre una persona con más experiencia o conocimiento y otra con menos competencia o experiencia; para otros autores, como Clutterbuck (2008), sin embargo, cada vez es más claro que coaching y mentoría deben ser defi nidos de manera diferente, relacionando el primero con el rendimiento en algún aspecto del trabajo o de la vida, y asociando al segundo más con el desarrollo integral y la promoción profesional. Ahondando más en esta distinción, Luecke (2004, p. 78) se decanta por una diferenciación respecto a su ámbito de aplicación.…”
Section: El Concepto De Mentoría Y Su Adecuación Al áMbito De La Formunclassified
“…The coaching manager may conduct formal coaching sessions or take the opportunity for informal coaching on a daily basis (Hunt and Weintraub 2002;Ellinger et al 2010;Wheeler 2011). Such coaching by managers is increasingly popular, with Clutterbuck (2009) reporting that a majority of organisations surveyed claimed that line managers could be effective or very effective coaches, while in his earlier paper, Clutterbuck (2008) suggested that the trend to equip all managers with coaching and mentoring skills was likely to accelerate, and indeed that some of those managers would develop sufficiently high levels of competence to enable them to provide support to other coaching managers.…”
Section: Communication Trustmentioning
confidence: 99%
“…All these roles have something in common in that all of them seek to help someone improve their performance by learning something new. Furthermore, they may draw on some of the same skills, so that the distinction relates more to where on the continuum the different activities fit, rather than the roles being complete opposites (Clutterbuck 2008;Lawton-Smith and Cox 2007).…”
Section: Role Switchingmentioning
confidence: 99%
“…AutorInnen diskutieren das Setzen von Zielen sei außer Kontrolle geraten und beklagen eine vermeintliche Über-verwendung von Zielen in Organisationen (Ordóñez et al 2009). Auch in der Coaching-Literatur werden die Grenzen von Zielsetzungen diskutiert (Clutterbuck 2008(Clutterbuck , 2010.…”
unclassified